How surrogacy arrangements fail children - TAN, Seow Hon (Institutional Knowledge at Singapore Management University, 2021)
Surrogacy arrangements are not in the best interests of children. When thinking about whether to legalize surrogacy, policy makers should consider the epigenetic effects of pregnancy, the loss to the children arising from separation from their birth mothers, and the special challenges associated with parenting by commissioning parents.